2016
DOI: 10.3109/0284186x.2015.1127414
|View full text |Cite
|
Sign up to set email alerts
|

The effect of training during treatment with chemotherapy on muscle strength and endurance capacity: A systematic review

Abstract: Background Treatment of cancer with chemotherapy decreases endurance capacity and muscle strength. Training during chemotherapy might prevent this. There are no clear guidelines concerning which type of training and which training dose are effective. This review aims to gain insight into the different training modalities during chemotherapy and the effects of such training to improve endurance capacity and muscle strength in order to obtain the knowledge to compose a future training program which trains cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Regardless of its association with mortality, resistance training is likely to be particularly important for cancer patients, as it helps to improve their muscle strength and specifically retains lean body mass. 35,36 This may help to protect patients from the adverse musculoskeletal effects of cancer treatments such as chemotherapy, as well as increasing quality of life and functional capacity compared with patients that do not participate in resistance training. 21,37,38…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of its association with mortality, resistance training is likely to be particularly important for cancer patients, as it helps to improve their muscle strength and specifically retains lean body mass. 35,36 This may help to protect patients from the adverse musculoskeletal effects of cancer treatments such as chemotherapy, as well as increasing quality of life and functional capacity compared with patients that do not participate in resistance training. 21,37,38…”
Section: Discussionmentioning
confidence: 99%
“…and habilitation (while undergoing cancer therapies; adjuvant) programs. Studies show that cardiovascular fitness is preserved or improved if exercise training is initiated prior to completion of cancer therapy, rather than waiting to recover cardiopulmonary function after completion of cancer therapy (105,106). This provides support for the benefit of habilitation even over rehabilitation.…”
Section: Potential Challenges In Cardio-oncology Prehabilitation Habmentioning
confidence: 86%
“…The health benefits of an active lifestyle during and after cancer treatment in the adult population have been described in the scientific literature. During cancer treatment, a systematic review of 14 RCTs in patients undergoing chemotherapy reported a positive effect of resistance and aerobic training in cardiorespiratory and muscular fitness 8. Likewise, a systematic review of 16 RCTs concluded that the practice of aerobic and/or resistance exercise during therapy (chemotherapy or radiotherapy) improved muscular strength 31.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity and exercise interventions are powerful tools associated with numerous benefits in terms of the HRQOL of cancer patients8–13 and survivors,9 10 14 15 including improvement in cardiorespiratory and muscular fitness, reduction in fatigue and improvement in body composition and well-being (ie, depression, anxiety, sleep quality and quality of life). As such, cancer patients and survivors have been encouraged to undertake regular exercise 16 17.…”
Section: Introductionmentioning
confidence: 99%